Prothrombin Complex Concentrate versus Fresh Frozen Plasma in Adult Patients Undergoing Cardiac Surgery: A Systematic Review and Meta-Analysis - Patricia Viana; Jessica Hoffmann Relvas; Marina Persson; Thamiris Dias Delfino Cabral; Jorge Eduardo Persson; Jessica Sales de Oliveira; Paulo Bonow; Camila Veronica Souza Freire; Sara Amaral (Journal of Chest Surgery, 2024)
Background: Prothrombin complex concentrate (PCC) and fresh frozen plasma (FFP) are commonly used to manage bleeding in patients during cardiac surgery. However, the relative efficacy and safety of these 2 strategies remain uncertain. Methods: MEDLINE, Embase, and Cochrane were searched for studies comparing PCC and FFP in patients who underwent cardiac surgery complicated by bleeding. Review Manager (RevMan) ver. 5.4 (Nordic Cochrane Centre, The Cochrane Collaboration) was used for statistical analysis. Binary and continuous outcomes were compared using pooled risk ratios and mean differences, respectively. The meta-analysis protocol was registered in the International Prospective Register of Systematic Reviews under protocol number CRD42022379144. Results: We included 8 studies with 1,500 patients, of whom 613 (40.9%) received PCC. The mean follow-up period ranged from 28 to 90 days. The PCC group had significantly lower chest tube drainage at 24 hours (mean difference [MD], -148.50 mL; 95% CI, -253.02 to -43.99 mL; p=0.005; I2=42%). Fewer units of red blood cells (RBCs) were transfused within the first 24 hours (MD, -1.02 units; 95% CI, -1.81 to -0.24 units; p=0.01; I2=56%), and fewer patients required RBC transfusion within the first 24 hours (risk ratio, 0.85; 95% CI, 0.78–0.93; p<0.007; I2=45%) in the PCC group. There were no statistically significant differences in secondary outcomes. Nonetheless, a subgroup analysis of randomized controlled trials failed to corroborate the results obtained from the main analysis. Conclusion: Our findings suggest that PCC can be effective, without increased adverse events, when compared with FFP in patients undergoing cardiac surgery complicated by bleeding.